Multilevel homology and discontinuity of person–group fit on individual and team creativity. Issue 2 (4th March 2023) - Seong, Jee Young; Choi, Jin Nam
ABSTRACT: We develop a multilevel framework that proposes the main and interactive effects of person–group (PG) fit in values and abilities on creativity at the individual and group levels. Our analysis of field data collected from 738 members comprising 108 work teams provides empirical support for our multilevel model of PG fit. Specifically, ability fit and collective ability fit exhibit consistent positive effects on individual and team creativity, respectively (i.e., multilevel homology). By contrast, at the individual level, value fit suppresses the positive effect of ability fit on individual creativity, while at the group level, collective value fit accentuates the positive effect of collective ability fit on team creativity (i.e., multilevel discontinuity). This study highlights the significance of multilevel interactive perspective on person–environment fit.